The Logic of Matthew 6.19-7.12: Heavenly Priorities in the Kingdom of Earth - Ridlehoover, Charles Nathan (New Testament studies, 2020)
In Sermon studies and their discussion of structure, scholars disagree on how to understand the latter half of the Sermon on the Mount (Matt 6.19-7.12). This section breaks the almost seamless structure of the first half of the Sermon (5.17-6.18). In what follows, I will argue that the latter half of the Sermon displays more structure than is generally acknowledged by Graham Stanton and others and gives us key insights into the overall message of the Sermon. I will argue that the structure of the latter half of the Sermon is marked by internal structuring, thematic consistency and verbal patterning. Matthew's emphasis in this section is on disciples having heavenly priorities while on earth.